Managerial Aversion and Capital Structure: Evidence from Southeast Asia - Yusuf Babatunde Adeneye,; Ei Yet Chu, (Asian Academy of Management Journal of Accounting and Finance, 2020)
This paper investigates the associations between managerial aversion, capital structure, and market valuation. The paper outlines managerial risk aversion and managerial regret aversion as perceptions of managerial aversion and tests whether both managerial behaviours directly affect the capital structure and market valuation of firms. The study uses a comprehensive measure of risk aversion by considering risk frequency, risk severity, and risk reduction price on shareholders’ equity. Using a data set of 860 Southeast Asian firms from 2007 to 2018, the study finds that managerial regret aversion affects market valuation and capital structure in market-based economies. Managerial risk aversion affects market valuation in both bank and market-based economies. Contrary to our hypothesis, managerial risk aversion has no significant effect on capital structure among Southeast Asian firms. The paper concludes that capital market undervaluation, leading to managerial aversion, has theoretical implications for regret theory of capital structure.